Comparison of physiological outputs of different maximum aerobic speed determination tests - Kirişci, İlker; Kızılet, Ali; Bozdoğan, Tuba Kızılet (Progress in Nutrition, 2020)
The aim of the study is to compare blood lactate, VO2max, HRmax, and RER values after the participants’ maximum aerobic speeds (MAS) are determined with 30 seconds running 15 seconds rest interval running test (30-15IFT), 45 seconds running 15 seconds resting area incremental interval running test (45-15FIT), and incremental treadmill tests. Materials and Methods: The participants of the study are fifteen athletes whose branches are football with an average age of 22.07 ± 0,69 years. Blood lactate values have been measured with portable lactate measuring device, VO2max with gas analyser, and heart rate with GPS running watch during the tests. SPSS 19.0 package program has been used for the statistical analysis of the study. Shapiro Wilk test has been used to assess the suitability of quantitative variables to normal distribution, Friedman test for the comparisons of non-normally distributed variables between 3 dependent groups, Wilcoxon test in 2 dependent group comparisons and Spearman correlation coefficient for the relations between quantitative variables. Results: When the data obtained at the end of 30-15IFT, 45-15FIT and treadmill tests were compared, a significant difference was found between the test- end  blood lactate (p=0,019), VO2max (p=0,006) and maximum aerobic speed (MAS) values (p